IMF Staff Papers, Volume 51, No. 3. (IMF Staff Papers; IMF Staff Papers ;, 2004)
This paper tests uncovered interest parity (UIP) using interest rates on longer maturity bonds for the Group of Seven countries. These long-horizon regressions yield much more support for UIP-all of the coefficients on interest differentials are of the correct sign, and almost all are closer to the UIP value of unity than to zero. The paper also analyzes the decision by a government facing electoral uncertainty to implement structural reforms in the presence of fiscal restraints similar to the Stability and Growth Pact.